Body mass index and socioeconomic status measured in adolescence, country of origin, and the incidence of gastroesophageal adenocarcinoma in a cohort of 1 million men. Issue 23 (15th October 2013) - Levi, Zohar; Kark, Jeremy D.; Shamiss, Ari; Derazne, Estela; Tzur, Dorit; Keinan‐Boker, Lital; Liphshitz, Irena; Niv, Yaron; Furman, Moshe; Afek, Arnon
Abstract : BACKGROUND: To the authors' knowledge, little work has been done concerning adolescent precursors for gastroesophageal cancer. In the current study, the association of adolescent overweight as well as socioeconomic status (SES) with the incidence of esophageal adenocarcinoma (EAC), gastroesophageal junction adenocarcinoma (GEJAC), and noncardia gastric cancer (NCGC) was evaluated. METHODS: Body mass index (BMI) was measured in 1 million Israeli adolescent males who underwent a general health examination at a mean age of 17.3 ± 0.5 years from 1967 to 2005. Overweight was defined as a BMI ≥ 85th percentile of the standard US distribution in adolescence. Incident cancer was identified by linkage with the Israeli National Cancer Registry. RESULTS: A total of 182 incident cancer cases were documented (52 combined EAC and GEJAC cases and 130 NCGC cases). Adolescent overweight at baseline (BMI ≥ 85th percentile) was associated with an increased risk in the combined group of cases of EAC and GEJAC (multivariable hazards ratio [HR], 2.1; 95% confidence interval [95% CI], 1.1‐4.3 [ P  = .032]). Low SES (the lowest category vs the highest) as well as low number of years of education (≤ 9 years) were associated with an increased risk of intestinal‐type NCGC (multivariable HR, 2.2; 95% CI, 1.0‐4.8 [ P  = .041] and multivariable HR, 1.9; 95% CI, 1.1‐3.19 [ P  = .020], respectively). The adjusted risk of NCGC was higher in immigrants born in Asian countries and the former Soviet Union. CONCLUSIONS: Overweight during adolescence was found to be substantially associated with the subsequent development of EAC and GEJAC. In addition, although potential confounding by Helicobacter pylori infection status or lifestyle factors was not fully accounted for in the analyses, lower SES as well as immigration from higher‐risk countries are important determinants of NCGC. Cancer 2013 ;119:4086–4093. © 2013 American Cancer Society . Abstract : Among the findings of the current study were that having a body mass index at or greater than the 85th percentile during adolescence is associated with the future development of adenocarcinoma of the lower esophagus and gastric cardia. In addition, a lower socioeconomic position at age 17 years is associated with a significantly increased risk of noncardia gastric cancer later in life.